2013
DOI: 10.1055/s-0033-1355407
|View full text |Cite
|
Sign up to set email alerts
|

Angst- und depressive Symptome und Gewaltexposition in der Wohnbevölkerung (60–84 Jahre) in Deutschland – Ergebnisse einer Querschnittstudie

Abstract: Our data suggest that exposure to violence in old age should be assessed to allow targeted prevention and intervention programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…30 In a study conducted in Germany, it was found that older adults who had been subjected to violence/abuse within the last 12 months had a risk of developing anxiety and depression. 53 Healthcare professionals are likely to encounter elder abuse on a routine basis; therefore, physicians and nurses are the professionals 54 who have an important place and role in the detection and management of abuse, as well as the treatment of subsequent psychiatric disorders. 55 Different types of universal, selective, and indicated interventions have been successful in protecting older populations from mental disorders such as depression and promoting mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In a study conducted in Germany, it was found that older adults who had been subjected to violence/abuse within the last 12 months had a risk of developing anxiety and depression. 53 Healthcare professionals are likely to encounter elder abuse on a routine basis; therefore, physicians and nurses are the professionals 54 who have an important place and role in the detection and management of abuse, as well as the treatment of subsequent psychiatric disorders. 55 Different types of universal, selective, and indicated interventions have been successful in protecting older populations from mental disorders such as depression and promoting mental health.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the important issue for psychiatric nurses is that the mental health of older adults who are subjected to abuse is at risk 30 . In a study conducted in Germany, it was found that older adults who had been subjected to violence/abuse within the last 12 months had a risk of developing anxiety and depression 53 . Healthcare professionals are likely to encounter elder abuse on a routine basis; therefore, physicians and nurses are the professionals 54 who have an important place and role in the detection and management of abuse, as well as the treatment of subsequent psychiatric disorders 55 …”
Section: Discussionmentioning
confidence: 99%